Analisis Imlementasi Projek Penguatan Pelajar Pancasila (P5) Tema: Kewirausahaan Pada Kurikulum Merdeka Belajar di Kelas IV SD GMIT 002 Kalabahi Tahun 2024 - Dekonius Mau Kallang; Jon A. Lalang Yame; Desi A. Tuaty; Adriana Elen Bana; Astri Rosita Mau Sally; Fidayanti Leki; Desi F. Tai Kaat (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to describe the implementation of the Project for Strengthening the Profile of Pancasila Students (P5) with the Entrepreneurship Theme in the Independent Learning Curriculum in Class IV Elementary School. This research was conducted in Class IV of SD GMIT 02 Kalabahi from April 20 to May 18 2024. This research approach was qualitative with a descriptive research type. The data sources for this research were 1 school principal, 1 class IV teacher, and all class IV students. Data collection techniques are carried out by observation and documentation. Data analysis techniques use reduction, data display, and verification. The results of the research show that the implementation of the Project for Strengthening the Profile of Pancasila Students with the Entrepreneurship Theme is quite good, namely that there are several implementations, namely forming a project implementation team and being independent, namely making flowers from straws. Identifying stages of school readiness in carrying out projects. Determine project dimensions, themes and time allocation. Compile project modules. Develop topics, activity flow, and Project assessments. The implementation of the P5 Entrepreneurship Theme has gone quite well with the culmination of the celebration holding a bazaar at the school. There are several steps in implementing the P5 project, namely starting, optimizing implementation, closing, and school involvement in project activities. Evaluation and follow-up on P5 of the Entrepreneurship Theme is to increase the entrepreneurial spirit because students are taught to make products that have selling value.